THE THINKING TRAJECTORY PROFILE OF STUDENTS TO PROVE THEOREM IN REAL ANALYSIS SUBJECT - Sri Suryanti (Universitas Muhammadiyah Gresik, 2016)
This study is a descriptive study aimed to describe students’ thinking trajectory inNproving theorem within real analysis I course. The subjects of this study are two students, man and woman who both have high academic ability based on GPA for courses in mathematics. The research instrument consists of researcher, interview sheet, interview guides and student worksheet that contains proving theorem. In this research the data analysis technique are data pruning, data presenting and conclusing. From the data analysis, it is obtained that the there is different thinking trajectory from the male andfemale subjects. The male student’s thinking trajectory: 1) At the information input stage, the subject understands well what is known and what will be proved, 2) at the informationprocessing stage, the subject is able to construct the proving steps correctly, the subject uses the definition available before, 3) within the information output step, the subject does not recheck the steps that he has written down, the subject gives answer illustration through pictures but he faces difficulty in explaining the picture. Female subject’s thinking trajectory : 1) at the information input stage, the subject understands well and she is able to write what is known and what is will be proved correctly, 2) at the stage of information processing, the subjects writes long and coherent steps , but there is a concept that has not been understood well , in constructing the proof, she does not use the existing definition, 3) at the information output stage, the subject re-checks the evidentiary steps which she writes previously, subject give answers with pictures and illustrations which she can explain well.